Soft palate (dulla) injuries in camels (Camelus dromedarius): clinical, hematobiochemical, histopathological findings and treatment outcomes - Sadan, Madeh; Aldakhil, Faris; Haridy, Mohie; Alshanbari, Fahad Abdullah; Refaai, Walid (Frontiers in Veterinary Science, 2026)
The soft palate, particularly the dulla, plays a crucial role in swallowing and maintaining airway function in dromedary camels (Camelus dromedarius). Damage to the dulla can negatively impact the health and productivity of these animals.AimThis study provides the first detailed description of the clinical, hematobiochemical, and histopathological features of soft palate (dulla) disorders, along with the surgical management of these conditions, in dromedary camels (Camelus dromedarius).MethodA total of 31 dromedary camels diagnosed with dulla disorders were examined through clinical, laboratory, and pathological evaluations.ResultsSeven distinct categories of dulla injuries were identified: lacerated wounds (7; 22.58%), protrusions (7; 22.58%), feed impaction (5; 16.12%), canine tooth puncture wounds (4; 12.9%), abscesses (3; 9.67%), hematomas (3; 9.67%), and gangrene (2; 6.45%). The clinical manifestations varied according to the type and duration of the lesion. Camels with entrapped dulla exhibited anorexia, neck stiffness with extension, and mild respiratory distress, whereas those with dulla protrusion showed swelling, fluctuation, and an inability to retract the dulla into the oral cavity. Analysis revealed A statistically significant increase in levels of sodium (p = 0.001), potassium (p = 0.008), phosphorus (p = 0.026), and ALT (p = 0.007), and a significant decrease in calcium (p = 0.012), glucose (p = 0.001), ALP (p = 0.034), and WBC (p = 0.03) levels after 2 weeks of treatment, as compared to pre-treatment and control values. The histopathology correlated with clinical findings and injuries varied in severity from erythematous mucosa to gangrene. The lesions included hemorrhages, erythematous mucosa, deep abscesses, lacerations with fresh ulcerations and old ulcers, foreign body pyogranuloma, and gangrene.ConclusionA combination of case history, clinical examination, hematobiochemical assessment, and pathological evaluation, together with surgical exteriorization of the dulla, enables an accurate diagnosis of soft palate disorders in dromedary camels. Furthermore, surgical excision of the affected dulla represents an effective and reliable therapeutic approach for managing these conditions in camels.